A randomized trial of a low‐dose Rasagiline and Pramipexole combination (P2B001) in early Parkinson's disease. Issue 5 (3rd April 2017) - Olanow, C. Warren; Kieburtz, Karl; Leinonen, Mika; Elmer, Lawrence; Giladi, Nir; Hauser, Robert A.; Klepiskaya, Olga S.; Kreitzman, David L.; Lew, Mark F.; Russell, David S.; Kadosh, Shaul; Litman, Pninit; et al.
ABSTRACT: Background: Rasagiline and pramipexole act to improve striatal dopaminergic transmission in PD via distinct and potentially synergistic mechanisms. We performed a placebo‐controlled study to determine whether 2 doses of a novel slow‐release, low‐dose combination of rasagiline and pramipexole (P2B001) are effective and have a good safety profile in patients with early untreated PD. Methods: Previously untreated patients with early PD were randomized (1:1:1) to once‐daily treatment with P2B001 (0.3 mg pramipexole/0.75 mg rasagiline), P2B001 (0.6 mg pramipexole/0.75 mg rasagiline) or placebo in a 12‐week multicenter double‐blind, placebo‐controlled trial. The primary endpoint was the change from baseline to final visit in Total‐UPDRS score versus placebo. Secondary measures included responder analyses of patients achieving ≥4 UPDRS point reduction, and changes in Parkinson Disease Quality of Life Scale–39 and UPDRS activities of daily living and motor scores. Results: A total of 149 participants were randomized and 136 (91.3%) completed the study. Adjusted mean change from baseline to final visit versus placebo in Total‐UPDRS score was −4.67 ± 1.28 points for the P2B001 0.6/0.75 mg group ( P = .0004) and −3.84 ± 1.25 points for the 0.3/0.75 mg group ( P = .003). Significant benefits were also observed for both doses in the responder analysis ( P = .0002 and P = .0001), Parkinson Disease Quality of Life Scale–39 scores ( P = .05 and P = .01), and the UPDRS motor ( P = .02 and P = .006) and activities of daily living ( P = .005 and P = .0004) subscores. Adverse events of P2B001 were comparable to placebo apart from transient nausea and somnolence, which were more common with P2B001 treatment. Conclusions: P2B001 offers a promising treatment option for patients with early PD with good clinical efficacy and a low risk of adverse events. © 2017 International Parkinson and Movement Disorder Society